PENGEMBANGAN DESAIN KEMASAN PRODUK CLEANER SEPATU YANG BERORIENTASI PADA KEPUASAN KONSUMEN DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Ahmat Abdul Muis Azzarkasi; Christian, Andrastea Zefta; M Faiq Hudaya Zulfa; Matias Junianto Wijoyo; Unggul Bayu Wicaksono; Andung Jati Nugroho (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2025)
Max Cleaning, as one of the MSMEs engaged in shoe washing services, has gained the trust of the public thanks to the quality of the washing carried out. Not only does it offer Max Cleaning services, it also sells its products, namely cleaners. Max Cleaning needs to develop packaging for its shoe cleaning products because competition is tight and product packaging is increasingly attractive, useful and at low prices, so it is necessary to develop packaging design. The development of shoe packaging cleaning designs that focus on consumer satisfaction using the Quality Function Deployment (QFD) method lies in the need to understand and fulfill customer preferences and needs in depth. The research objective is to provide an improved design for shoe cleaning packaging products that suit customer needs. Data collection techniques used in research to obtain data from respondents using questionnaires. Based on 5 attributes that influence customer satisfaction, it has a high level of satisfaction and is needed by consumers, namely the unique shoe cleaner packaging product design influences the decision to buy" with a value of 3.39. Based on the analysis of raw weight, the attribute developed is an environmentally friendly packaging product. And packaging improvements have been added with detailed information on the ingredients, as well as how to use the shoe cleaner, adding to the value of the shoe cleaning product packaging. Added to this, the striking color of the logo design gives brightness and a unique impression to the packaging. Changing the material from previously 50% alcohol to 10% alcohol content, this is more effective and safe for the user's health and does not damage the shoe material.